2022
DOI: 10.1186/s12889-022-14579-7
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic impact of tuberculosis on children and adolescents: a scoping review and conceptual framework

Abstract: Background Tuberculosis (TB) has been repeatedly shown to have socioeconomic impacts in both individual-level and ecological studies; however, much less is known about this effect among children and adolescents and the extent to which being affected by TB during childhood and adolescence can have life-course implications. This paper describes the results of the development of a conceptual framework and scoping review to review the evidence on the short- and long-term socioeconomic impact of tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Therefore, improving the socioeconomic status of households through economic empowerment would help to decrease the prevalence of malnutrition among children under the age of 5 years. Atkins et al ( 2022 ) attest that TB has been repeatedly shown to have socioeconomic impacts in both individual level and ecological studies; however, much less is known about this among children and adolescents and the extent to which being affected by TB during childhood and adolescence can have life-course implications. Therefore, despite the negative impact on children’s caregivers regarding paediatric nutrition during TB treatment, possible solutions to compensate for or reverse this are of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the socioeconomic status of households through economic empowerment would help to decrease the prevalence of malnutrition among children under the age of 5 years. Atkins et al ( 2022 ) attest that TB has been repeatedly shown to have socioeconomic impacts in both individual level and ecological studies; however, much less is known about this among children and adolescents and the extent to which being affected by TB during childhood and adolescence can have life-course implications. Therefore, despite the negative impact on children’s caregivers regarding paediatric nutrition during TB treatment, possible solutions to compensate for or reverse this are of importance.…”
Section: Discussionmentioning
confidence: 99%
“…The holistic impact of TB on well-being, finances and quality of life requires the simultaneous provision of biomedical and socioeconomic approaches to control TB, which in turn requires intersectoral collaboration especially between healthcare and social sectors. [14][15][16] However, despite a high proportion of people with TB and their households being economically vulnerable and likely to benefit significantly from social support, they are rarely covered by social support policies.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Therefore, there is a growing consensus that progress towards the ‘End TB Strategy’ targets will require not only investment in strengthening biomedical responses through improving access and effectiveness of healthcare delivery12 but also actions on the socioeconomic determinants and consequences of TB, as well as measures to improve quality of life and well-being after TB-episode,3 4 10 13 especially in low- and middle-income countries. The holistic impact of TB on well-being, finances and quality of life requires the simultaneous provision of biomedical and socioeconomic approaches to control TB, which in turn requires intersectoral collaboration especially between healthcare and social sectors 14–16. However, despite a high proportion of people with TB and their households being economically vulnerable and likely to benefit significantly from social support, they are rarely covered by social support policies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations